2019
DOI: 10.1177/2055207619896145
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on defining the scope and development of text-based coaching protocols for digital mental health interventions

Abstract: A body of literature suggests that the provision of human support improves both adherence to and clinical outcomes for digital mental health interventions. While multiple models of providing human support, or coaching, to support digital mental health interventions have been introduced, specific guidance on how to develop coaching protocols has been lacking. In this Education Piece, we provide guidance on developing coaching protocols for text-based communication in digital mental health interventions. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…This mirrors data from clinical trials of in-person care for anxiety, where the largest effects are for those who receive more frequent sessions. This is also consistent with most evidence-based protocols of 8-12 sessions, as these sessions are not always completed at a weekly cadence [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This mirrors data from clinical trials of in-person care for anxiety, where the largest effects are for those who receive more frequent sessions. This is also consistent with most evidence-based protocols of 8-12 sessions, as these sessions are not always completed at a weekly cadence [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…In general, a typical treatment period consists of 8-12 weeks, with weekly interactions to check in on progress. However, there are certain situations in which the duration of treatment is modified (either extended or shortened) based on member-specific circumstances (clinical presentation, covered sessions, the goodness of fit between clinician and member, and life circumstances), which is consistent with recommendations from the literature [ 17 , 32 ]. For example, Ginger clinical protocols state that maintenance and termination can be considered if there is a response by 4-8 weeks.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…However, the qualification of eCoaches has minor importance for the outcome ( Baumeister et al, 2014 ). Further, the differences in previous experiences are minimised by using message templates and by the possibility to discuss with senior researchers ( Lattie and Graham, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review concluded that health coaching could motivate change in the lifestyle behavior of patients with chronic illness, leading to improvements in both physical and mental health status [15]. Recent studies focused on text-based coaching interventions have shown significant improvements in mental health outcomes equivalent to treatment as usual, namely, in-person and telephone counseling [16,17]. Because there can be significant heterogeneity in these types of interventions, researchers and clinicians have published guidance on developing protocols for text-based coaching in digital mental health interventions [17].…”
Section: Treatmentmentioning
confidence: 99%